Fading out effect or long lasting nudge? The impact of a conditional cash transfer program beyond starting the school year in Argentina - María Edo; Mariana Marchionni (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2018)
We estimate the impact on education outcomes of the Universal Child Allowance (AUH), a massive conditional cash transfer program targeted at young children of unemployed and informal workers launched in Argentina in late 2009. Evidence from previous works suggests that the AUH has had a significant positive impact on attendance rates at the beginning of the school year, but concentrated on boys in upper-secondary school. In this paper we study the effects on other education outcomes: intra-year dropout rates and primary school completion rates. We find that the AUH may be held responsible for significant improvements in both outcomes while the analysis highlights heterogeneous effects across age groups and gender. In particular, the AUH seems to have contributed to reduce intra-year dropout rates of eligible girls aged 12 to 14 (almost 4 p.p.) and 15 to 17 (7 p.p.) while no effects were found for children aged 6 to 11 or for boys, irrespective of age. The program seems to have also increased the probability of graduating from primary school of over-aged eligible children (1.4 p.p. for boys aged 12 to 14, almost 3 p.p. for girls in that age range and 2 p.p. for boys in the 15-17 age group). These results suggest that beyond the effects on school access indicators, the AUH may also contribute to the improvement of final outcomes in education. Nevertheless, the evidence also indicates that there is room for improvements in the design of the program aimed at enhancing these long term effects.
Keywords: I2; I3; 330; conditional cash transfers; education; gender; Argentina; AUH